2006
DOI: 10.1111/j.1600-0609.2006.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor promoter gene polymorphism associated with increased susceptibility to non‐Hodgkin's lymphomas

Abstract: The tumor necrosis factor (TNF) is a pro-inflammatory cytokine involved in the severity of different immune-regulated diseases including autoimmune, infectious, and malignant diseases. Chronic immune system stimulation could be a potential etiologic factor in these diseases. Given the determining role of TNF acting early in the immune response, we investigated the effect of an inherited genetic polymorphism at TNF promoter (-308A/G) on a predisposition to non-Hodgkin's lymphoma (NHL). The genotype distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…Nonetheless, in one of the participating US studies [11] the TNF rs1800629 AA genotype was associated with a four-fold increased risk of T-cell lymphoma. An association between TNF rs1800629 and risk of NHL was also observed in a small study among whites in North Africa [9], but not in an Australian study [10]. The Australian study reported however that IL10 rs1800890 variant allele homozygosity conferred an 80% higher risk of DLBCL [10].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nonetheless, in one of the participating US studies [11] the TNF rs1800629 AA genotype was associated with a four-fold increased risk of T-cell lymphoma. An association between TNF rs1800629 and risk of NHL was also observed in a small study among whites in North Africa [9], but not in an Australian study [10]. The Australian study reported however that IL10 rs1800890 variant allele homozygosity conferred an 80% higher risk of DLBCL [10].…”
Section: Discussionmentioning
confidence: 84%
“…To date, the most consistent findings across studies are associations of genetic variation in the tumor necrosis factor (TNF) gene, but also in interleukin-10 (IL10), with risk of NHL [7][8][9][10][11][12][13]. The TNF gene regulates the expression of the cytokine TNF-a, which gives rise to the inflammatory response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic studies showed that SNPs from candidate genes, including TNF (10,(12)(13)(14); LTA (10); IL4, IL5, and IL6 (11); and IL10 (10)(11)(12)14), may be risk factors for NHL overall or for certain NHL subtypes. Our study showed evidence of a possible role of TNF-α in lymphomagenesis, particularly B-NHL.…”
Section: Mori Et Al (25) Studied Cd4mentioning
confidence: 99%
“…Biological markers related to the immune system such as cytokines have been studied to explain the etiology of NHL (14)(15)(16). However, there are only few studies that have studied cytokine levels prospectively in relation to NHL risk and none have been in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47][48] The TNF gene regulates the expression of the cytokine TNF-␣, which gives rise to the inflammatory response to infection. Furthermore, high levels of TNF-␣ promote activation of the transcription factor nuclear factor-B, which has antiapoptotic effects on B cells.…”
Section: Discussionmentioning
confidence: 99%